EVALUASI KINERJA OPERASIONAL DAN USAHA PENANGANAN KEMACETAN LALU LINTAS PADA SIMPANG RING ROAD UTARA – JALAN KALIURANG, SLEMAN, DI YOGYAKARTA - Yuliani, Amri Rizky; Mulyaningrum, Febrina Tri; Wicaksono, YI.; Supriyono, Supriyono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Yogyakarta is a very strategic because it is located in the middle of the south line of Java, which is a traffic brokering eastern Java and West Java. Each year the vehicle across the city of Yogyakarta has increased, besides due to its tourism appeal, Yogyakarta factors as student city became the main drivers of traffic congestion, especially at the strategic intersection of the Ring Road intersection north-Way Ground. From the secondary data obtained from the Directorate General of Highways Yogyakarta showed that the rate of growth in daily traffic average intersection has increased in the last 5 years. Figures show the feasibility of the service with the highest degree of saturation / degree of saturation (DS), the condition on the road DS> 0.75 and at the intersection of DS> 0.85. The results of the analysis of primary data obtained from the field survey in January 2013 showed the value of DS on existing roads still eligible, while the value of DS intersections are not eligible. Basic steps of handling the problem of congestion, namely the optimization of intersections with signal timing, intersection geometry settings and traffic management. After these steps are considered not provide significant changes in the value of DS, the last step is planning the construction of new roads in the form of flyover. With the construction of new roads, intersection capacity will be increased so that the value of DS who qualify will last a long time with increasing growth rate LHR Yogyakarta city in the years to come.